The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ufug.2019.126383
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Environmental Aesthetic Qualities Scale (PEAQS) – A self-report tool for the evaluation of green-blue spaces

Abstract: Aesthetic qualities of urban green and blue spaces have received considerable attention in scientific literature but are operationalized in multiple ways and lack clear assessment and measurement techniques. To fill in this gap, we developed a Perceived Environmental Aesthetic Qualities Scale (PEAQS). Based on previous literature both in philosophy and empirical sciences we created a questionnaire with 36 statements and three open questions focusing on the perceived aesthetic qualities of environments. This qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…In cultural and creative tourism, perceived aesthetics and enjoyment are essential elements of aesthetic value [32]. Perceived aesthetics is the aesthetic response of one or more senses to environmental stimuli, which will affect individual information processing after being internalized, such that aesthetic quality can be regarded as the result of the interaction between individuals and the environment [46]. When tourists perceive aesthetics in tourism activities, the impact of the tourism destination environment on the tourist experience is direct and profound [47].…”
Section: Perceived Aestheticsmentioning
confidence: 99%
“…In cultural and creative tourism, perceived aesthetics and enjoyment are essential elements of aesthetic value [32]. Perceived aesthetics is the aesthetic response of one or more senses to environmental stimuli, which will affect individual information processing after being internalized, such that aesthetic quality can be regarded as the result of the interaction between individuals and the environment [46]. When tourists perceive aesthetics in tourism activities, the impact of the tourism destination environment on the tourist experience is direct and profound [47].…”
Section: Perceived Aestheticsmentioning
confidence: 99%
“…Through semi-structured interviews, the analysis yielded 21 aesthetic dimensions, which were grouped into nine themes. Subiza-Pérez et al [31] developed the PEAQS to measure the aesthetic quality of a tourist attraction, but the scale only focuses on the aesthetics of the natural physical environment and does not address the deeper emotional and spiritual aspects of aesthetics. Breiby et al [32] construct an aesthetic experience scale with five dimensions from sensory aspects: "harmony", "variation/contrast", "scene/viewing", "genuineness", and "art/architecture".…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the study of aesthetic experience focuses on philosophical discussion so that empirical research on the aesthetic experience offered by tourism is needed [30]. A small number of empirical studies mainly focus on the "sensory level" of aesthetic experience [31][32][33], ignoring its "spiritual level". In fact, the existing literature tends to regard aesthetic experience as a dimension of consumer experience (entertainment, education, aesthetics, and escape) [34], and research focuses on the role of aesthetic experience in the field of service marketing [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of previous studies have indicated that the beneficial effects of landscape preferences and rehabilitation landscapes on humans' physical and psychological health will be affected by a person's attention to nature, sense of fatigue, and other psychological states (Berman et al, 2009;Tyrväinen et al, 2014;van den Berg and Jorgensen, 2014;Windhorst and Williams, 2015). Although Joye and van den Berg (2011) have pointed out that landscape preference was not a direct cause of physical and mental recovery, it is undeniable that in the studies on landscape preference, there is a positive correlation between a psychological state and a healthy relationship (Hartig et al, 1997;van den Berg et al, 2003;Subiza-Pérez et al, 2019); the researchers considered that people are more likely to choose to ascend in their well-being and emotional state of active space (Kaplan et al, 1998;Feng and Chen, 2020). Although moods cannot be totally equal to emotions, moods are often used as indicators of emotion to explore the benefits of nature to human beings.…”
Section: Psychological-affective Mood and Landscape Preferencementioning
confidence: 99%